Insights on the Optical Properties of Estuarine DOM - Hydrological and Biological Influences. - Luísa Santos; António Pinto; Olga Filipe; Ângela Cunha; Eduarda B H Santos; Adelaide Almeida (PLoS ONE, 2016)
Dissolved organic matter (DOM) in estuaries derives from a diverse array of both allochthonous and autochthonous sources. In the estuarine system Ria de Aveiro (Portugal), the seasonality and the sources of the fraction of DOM that absorbs light (CDOM) were inferred using its optical and fluorescence properties. CDOM parameters known to be affected by aromaticity and molecular weight were correlated with physical, chemical and meteorological parameters. Two sites, representative of the marine and brackish water zones of the estuary, and with different hydrological characteristics, were regularly surveyed along two years, in order to determine the major influences on CDOM properties. Terrestrial-derived compounds are the predominant source of CDOM in the estuary during almost all the year and the two estuarine zones presented distinct amounts, as well as absorbance and fluorescence characteristics. Freshwater inputs have major influence on the dynamics of CDOM in the estuary, in particular at the brackish water zone, where accounted for approximately 60% of CDOM variability. With a lower magnitude, the biological productivity also impacted the optical properties of CDOM, explaining about 15% of its variability. Therefore, climate changes related to seasonal and inter-annual variations of the precipitation amounts might impact the dynamics of CDOM significantly, influencing its photochemistry and the microbiological activities in estuarine systems.